Penyelesaian Sengketa Dalam Perjanjian Kerjasama Penjualan Kavlingan Tanah di Desa Ranah Sungkai Kecamatan XIII Koto Kampar Kabupaten Kampar - Rukmana, Hermi; Lestari, Rika; Dasrol, Dasrol (Jurnal Ilmiah Wahana Pendidikan, 2024)
Humans in fulfilling their needs are inseparable from the assistance and cooperation carried out, often in which an agreement has been made. The Cooperation Agreement for the Sale of Land Lots between PT Kawasan Kurma Indonesia, which is engaged in property along with gardens, complete with a Sharia-based Muslim area with landowners, however, there are rights from landowners that are not paid. The formulation of the problem in this thesis is how efforts to resolve disputes in the land kaflingan sales cooperation agreement in Ranah Sungkai Village, XIII Koto Kampar District, Kampar Regency and what are the inhibiting factors in dispute resolution efforts in the land kaflingan sales cooperation agreement in Ranah Sungkai Village, XIII Koto Kampar District, Kampar Regency. This type of research is sociological research because with this research the author directly conducts research at the location or place under study, namely to provide a complete and clear picture, while the population and samples are the Head of Ranah Sungkai Village, the landowner community and the Manager of Corporate Aaffairs / Legal / HRIR PT Kawasan Kurma Indonesia. The purpose of this research is to find out the Dispute Resolution in the Cooperation Agreement for the Sale of Land Plots in Ranah Sungkai Village, XIII Koto Kampar District, Kampar Regency and the obstacles to Dispute Resolution in the Cooperation Agreement for the Sale of Land Plots in Ranah Sungkai Village, XIII Koto Kampar District, Kampar Regency.The results of this study are efforts to resolve disputes in the land kaflingan sales cooperation agreement in Ranah Sungkai Village, XIII Koto Kampar District, Kampar Regency have been carried out and the result is an agreement to disagree, because the mediation process does not get an agreement as well as the consensus deliberation process and inhibiting factors Both parties maintain their arguments and insist on their respective opinions There is no good faith from each party to the dispute. The parties do not understand the mediation process and the selfishness of the parties. The author's suggestion for the parties involved in resolving disputes in the land kaflingan sales cooperation agreement in Ranah Sungkai Village, XIII Koto Kampar District, Kampar Regency is to carry out a subpoena, if the subpoena has been taken also does not get results, proceed to the district court which is mutually agreed upon according to the agreement.